Modelling and simulation in management research (2017)
Although the field of modeling and simulation has developed significantly for several decades, its use in management research is relatively recent, and particularly in Latin America its development can not be considered as extensive in schools and their research units. The work introduces most relevant concepts, contributions and limitations of the M and S, its main philosophical aspects and its most outstanding fields and tools. © 2017. revistaESPACIOS.com.